Customer relationship management Celcom (Malaysia) Sdn Bhd - Abdul Aziz, Sharizan (2002)
Celcom (M) Sdn Bhd is a leading provider of telecommunication services. This case looks at Celcom's business issues in terms of customer satisfaction amidst a volatile industry, increasing competition and evolving market share. Celcom is faces with a lot of business challenges in view of eroding market brought about by stiff competition and reduction in service level delivery. Analysis will be made both on the organization as well as on Celcom's current customer base and its various Customer Relationship Management initiatives and loyalty programs to examine its effectiveness in sustaining growth revenue. The course of action recommended is to stay focus in areas of core competencies and in the process recapture the market leadership position. Being a customer focused organization it is also recommended that customer relationship management initiatives be further strengthened and emphasized.